2018
DOI: 10.1016/j.msard.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines and the association with relapses in patients with neuromyelitis optica spectrum disorder

Abstract: The evidence suggests that there may be a risk of vaccination-associated relapses among untreated neuromyelitis optica spectrum disorder patients, however immunosuppressive therapy at time of vaccine may abort the risk; this suggests that the patients who are treated with preventive immune suppression and receive routine vaccinations for common infections may fare better. Further prospective studies are necessary to verify these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…However, there is concern for vaccine-induced relapse, as live vaccines usually produce stronger immune responses, especially in the absence of immunotherapy. Indeed, vaccine studies in neuromyelitis optica have shown increased risks of vaccine-related relapses in untreated patients while treated patients were protected (Mealy et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is concern for vaccine-induced relapse, as live vaccines usually produce stronger immune responses, especially in the absence of immunotherapy. Indeed, vaccine studies in neuromyelitis optica have shown increased risks of vaccine-related relapses in untreated patients while treated patients were protected (Mealy et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Onset of relapse symptoms can occur in up to 90 days following vaccination but the incidence is highest at 30 days. Those on preventive immunotherapy for NMOSD have an 81% lower risk of disease relapse following vaccinations [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccines are intended to provide protection against specific antigens, but in ramping up an immune response, rogue autoimmune elements may also become activated and potentially trigger an unwanted attack. Vaccine-associated attacks have been linked to neuroimmunological disorders including TM, optic neuritis, ADEM, and NMOSD (Agmon-- Levin et al, 2009;Huynh et al, 2008;Karussis and Petrou, 2014;Mealy et al, 2018;Zanoni et al, 2002). Infections are also potent triggers of attack; more than 40 cases of TM following COVID have been reported (Mondal et al, 2021;Schulte et al, 2021).…”
Section: Discussionmentioning
confidence: 99%